Pengaruh Bauran Pemasaran Sumber Daya Manusia (SDM) terhadap Loyalitas Pasien Rumah Sakit: Systematic Review - Primasari, Elsa (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
In today's fast-paced era of information and technology, there is also a demand for advancements in healthcare services, particularly hospitals. Currently, more and more hospitals are being established in Indonesia, resulting in increased competition among them. Therefore, hospitals must innovate by utilizing the marketing mix, especially the human resources factor, to maintain patient loyalty. This article aims to determine the influence of the human resources marketing mix on patient loyalty in hospitals. This study uses a systematic review design. The search was conducted using the keywords "Human Resources Marketing Mix," "Patient Loyalty," "Influence," AND "Hospital." The article search was accessed from internet databases, namely Proquest and Google. An initial identification found 49 articles on Proquest and 45 on Google Scholar. We then screened them for relevance, and after screening according to the inclusion criteria, only six articles were included. After a full article screening and eligibility process, five articles were found to be relevant to the discussion of the influence of the human resources marketing mix on patient loyalty. Of the five reviewed articles, four mentioned that the human resources marketing mix significantly influencestient loyalty to hospitals. Only one article stated that staff/human resources do not have a substantial influence on hospital patient loyalty. The human resources marketing mix factor affects patient loyalty. Human resources are the critical factor in the success of hospital service marketing. Good behavior, character, integrity, and professionalism of human resources are the main assets in maintaining patient loyalty.